A REVIEW ON CHANGED CONSUMER BEHAVIOR DURING COVID-19 CRISIS - Mishra, Dr. Anjan (The journal of contemporary issues in business and government, 2020)
Human behavior is pushed in many directions by a critical situation, with certain aspects of behavior being irreversible. Because the COVID-19 pandemic is not a typical crisis, several methods were implemented to restrict the disease’s spread, including complete and then partial lockdown. Because all aspects of the economy are inextricably intertwined with public health measures and lockdown, the nations’ economies have become unstable, indicating a shift in market dynamics. Customers are the drivers of competition in the market, growth, and economic integration in any market. Consumer behavior is changing as a result of economic uncertainty, albeit how much of the change witnessed during the crisis will last remains to be seen. This essay examines consumer behavior during the COVID-19 crisis and the accompanying global standstill that lasted over a quarter of a year. Furthermore, the article tries to weave through the maze of available literature about consumer behavior in regular and downturn times, strengthens it with rapid review culled out by various consulting organizations during the lockdown stage, and substantiates the same with first-hand telling and retelling of experiences by consumers and professionals with marketing backgrounds to bring up a hypothesis of the pandemic causing a paradigm shift where consumer spiritualism has evolved from consumer materialism. The thesis proposes more testable hypotheses for future study to better understand consumer attitudes or requirements in purchasing "what is enough" in a marketing setting, and how this may be reinforced post-COVID crisis to ensure business model sustainability. To build new consumer behavior theories, researchers should investigate the correlations of this forced consumer behavior with other variables such as learning from crises, changing demands, personality, nationality, culture, emerging market segment, and age.